Differentiation-related changes in lipid classes with long-chain and very long-chain polyenoic fatty acids in rat spermatogenic cells - Oresti, Gerardo Martin (2010)
In rat seminiferous tubules (ST), cells that contain polar and neutral lipids with long-chain polyenoic fatty acids (PUFA) and sphingomyelins (SM) and ceramides (Cer) with very long chain (VLC) PUFA of the n-6 series coexist. In this study, pachytene spermatocytes and round spermatids were isolated to determine how these lipids change during spermatogenesis. As the amount per cell of PUFA-rich glycerophospholipids (GPL) decreased with cell size, the 22:5/20:4 ratio increased with cell differentiation. The elovl2 and elovl5 genes, required for 22:5 formation, were expressed (mRNA) in both cell types. Residual bodies- particles with compacted organelles and materials discarded from late spermatids-concentrated cholesterol, 22:5-rich triacylglycerols, and GPL, including plasmalogens and phosphatidylserine. Species of SM and Cer with nonhydroxylated (n-) VLCPUFA (28:4, 30:5, and 32:5) predominated in pachytene spermatocytes, whereas species with the corresponding 2-hydroxy (2-OH) VLCPUFA prevailed in round spermatids. Thus, a dramatic increase in the 2-OH/n-VLCPUFA ratio in SM and Cer was a hallmark of differentiation. A substantial decrease of 2-OH SM occurred between spermatids and mature spermatozoa and 2-OH SM species were collected in residual bodies “en route” to Sertoli cells. Notably, spermatids and spermatozoa gained a significant amount of ceramides devoid of n-VLCPUFA but having 2-OH VLCPUFA as their main fatty acids.